Azcapotzalco antes que Tenochtitlan: reflexiones en torno a un modelo azteca de imperio - Santamarina Novillo, Carlos (Revista Española de Antropología Americana, 2007)
This paper proposes the consideration of an Aztec empire model that includes two hegemonic phases during the Late Postclasic Period in the central area of Mesoamerica: the Tepaneca and the Mexica. I revise Ross Hassig’s proposal about hegemonic domination. From this analysis, a concept called postconquest politics is proposed, referring to the decisions made by the hegemonic center, before war, in order to articulate a local level into its system of domination. Azcapotzalco’s history is also examined, as a Tepaneca hegemonic polity that was able to unite under its domination the entire lake area and other more distant territories. This system provided the foundation for the subsequent development of the Mexica Empire. The Aztec process of centralization in the lake area was begun under Tepanec rule, and was then continued and developed under Mexica rule, but not without going through a crisis known today as Tepanec war.